Developmental Trajectories of Marijuana Use among Men: Examining Linkages with Criminal Behavior and Psychopathic Features into the Mid-30s. (November 2015) - Pardini, Dustin; Bechtold, Jordan; Loeber, Rolf; White, Helene
Objectives: Examine whether young men who chronically use marijuana are at risk for engaging in drug-related and non-drug-related criminal offending and exhibiting psychopathic personality features in their mid-30s. Methods: Patterns of marijuana use were delineated in a sample of predominately Black and White young men from adolescence to the mid-20s using latent class growth curve analysis. Self-report and official records of criminal offending and psychopathic personality features were assessed in the mid-30s. Analyses controlled for multiple factors indicative of a preexisting antisocial lifestyle and co-occurring use of other substances and tested for moderation by race. Results: Four latent marijuana trajectory groups were identified: chronic high, adolescence-limited, late increasing, and low/nonusers. Relative to low/nonusers, chronic high and late increasing marijuana users exhibited more adult psychopathic features and were more likely to engage in drug-related offending during their mid-30s. Adolescence-limited users were similar to low/nonusers in terms of psychopathic features but were more likely to be arrested for drug-related crimes. No trajectory group differences were found for violence or theft, and the group differences were not moderated by race. Conclusions: Young men who engage in chronic marijuana use from adolescence into their 20s are at increased risk for exhibiting psychopathic features, dealing drugs, and enduring drug-related legal problems in their mid-30s relative to men who remain abstinent or use infrequently.